Legal Review of Local Government Institutions in Papua under Government Regulation No. 106/2021 - Billy Muskitta Bastian Erlando; Vieta Imelda Cornelis; Noenik Soekorini; Sri Astutik; Hartoyo Hartoyo (Journal of International Multidisciplinary Research, 2025)
The Province of Papua holds a special constitutional status under Law No. 2 of 2021, implemented through Government Regulation (PP) No. 106 of 2021, which assigns 23 governmental functions to regional authorities. The regulation embodies asymmetric decentralization intended to protect the rights of Indigenous Papuans (OAP) and address local needs. However, it raises legal concerns regarding ambiguous authority distribution between central, provincial, and municipal levels, as well as the unclear operational role of the Papuan People’s Assembly (MRP). The main research problem is whether PP No. 106/2021 provides a coherent and constitutionally consistent governance framework. This study applies doctrinal legal research using normative-analytical methods, including statutory interpretation, constitutional tests, and comparative perspectives. The findings indicate weak accountability mechanisms in managing Special Autonomy Funds, limited integration of customary law, and institutional fragility in newly established bodies such as BP-DOP and UPAP. The study concludes that PP No. 106/2021 does not fully align with the constitutional principles of legal certainty and decentralization. It recommends substantial revisions, strengthening MRP’s legal status, formal recognition of customary law through Perdasus, and an institutional blueprint with clear performance indicators to ensure effective, inclusive, and adaptive governance in Papua